MANTRA BAHASA ENDE DI DESA UZUZOZA KABUPATEN ENDE - Alexander Bala (SASTRANESIA: Jurnal Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2020)
The research is about the spell of Ende Language in Uzuzoza village of Ende Regency based on two main problems, that was finding and describing spell’sform and it’s function. For gathering the data, the research used was an interview and listen tomethod with see, and capable techniques. Formal technique analysis is usedas data analysis of this research. The old theory of literature is used of this research with the concideration that the spell developed in the traditional era in animism and dynamism by using oral languageas the main medium of its delivery. After the data were analysis, the result found that, the spell of Ende language in Uzuzoza village of Ende Regency is generally in the form of poetry because taxtation patters were a-a-a-a, have taxtation (rhymes), expecially intonation, that is the persuasion of vowels at the and of word in lines and the linesof that spells is contentsor messages. Lingustically, the spells using personal pronouns, expecially the use of second personal pronouns and third personal pronouns using repetation, and it consistof statement which has adverb of time, adverb of place, and indicating of prohibition. Funcionality, the spell of Ende language in Uzuzoza village of Ende Regency serves as the tribute the “highest” subject which makes them exist and as the symbol of their trus to the ancestors.